A Case-research of Teacher-Driven PLC in a Hierarchical Organization: An Ecological Framework with Highlight in Adult Learning - Adiya Alimujiang; Qian Wang (Adult Education Research Conference, 2023)
Inspired by the organizational learning philosophy, this study developed an ecological framework and applied it to examine the mechanism of a Chinese fee-paying school’s teacher professional learning activities.
Keywords: Ecological PLC Framework; Organizational Learning; Professional Learning Community; Teacher Education